Diseases of Tropical Pines in Central India - , Jamaluddin; Soni, K. K. (Indian Forester, 2006)
Tropical pines are being increasingly used in pulp and paper industry and to meet their increased demand these are being raised in plantations. Exotic and indigenous plant species are seen to suffer from various diseases. Of these, damping off of Pinus caribaea in nursery beds can be controlled by drenching the soil mix with Blitox or Fytolan. Cercospora needle blight is seen affecting P.caribaea and P.roxburghiana. Fungicides Bavistin and Dithane can be applied during monsoon period to check spread of this disease. Lophodermimam needle fall is caused by various pathogens but the damaged caused is insignificant as the pathogens are rather weak. Diplodia die back in P.caribaea plantation was seen to affect poorly growing plants and is almost absent in vigorously growing trees. Charcoal root rot in P.caribaea can be managed by modifying nursery practices such as weeding out leguminous weeds, avoiding intercropping, avoiding fertilizers during nursery stage, planting replacements in fresh pits, so that infection does not take place.